Enhancing Muslim Consumer Purchasing Decisions: The Impact of Product Quality, Price, Service Excellence, and Halal Certification - Amanda, Dinda Ardelia; Santosa, Perdana Wahyu (SAN Scientific, 2024)
This research aims to determine the influence of Product Quality, Price, Service Quality, and Halal Certification on Muslim Consumer Purchasing Decisions at